"Meet Them Where They Are": Attentional Processes in Social Movement Listening. Issue 4 (4th January 2021) - Johnson, J. L.
Abstract : I draw on Erving Goffman's Frame Analysis and Eviatar Zerubavel's sociology of attention to examine social movement communication as attempts to change hearts and minds by changing definitions of social problems. Specifically, I ask: When and how do bystanders entertain affective and cognitive disruptions? By what processes do movement bystanders listen to movements? I conceptualize social movement listening as a set of processes by which bystanders might entertain the affective and cognitive disruptions necessary for considering broader claims and symbols of movement activism. I demonstrate three types of attempts by movement actors to successfully create these listening possibilities: anchoring selves into social movements, accommodating anti‐criticalness, and reversing attentional socialization.